Exploring the vitality of Tianjin’s downtown based on the Light GBM-SHAP model - Na Li; Li Yao (Computational Urban Science)
Abstract In the age of stock planning, urban vitality is a key indication of a city’s health and vitality. Using the central city of Tianjin as an example, the study uses multi-source data, such as Weibo check-ins, points of interest, etc., to quantify urban vitality. The Light GBM-SHAP model is chosen to measure the non-linear effects of each indicator on urban vitality in four dimensions: crowd vitality, economic vitality, facility vitality, and environmental vitality. The study also applies spatial visualization and spatial statistical analysis to analyze the vitality of the central city of Tianjin in terms of time and space scales. The findings indicate that: (1) There is clear temporal and geographical variation in the vitality distribution in Tianjin’s core urban region. Over time, spring, particularly April, is marked by a surge of vitality brought on by the tourist season and holiday effects; there is a double-peak time in the morning and evening, and the nighttime vitality is particularly strong; and, in terms of space, urban vitality tends to decline from the Heping District outward. (2) Public facility density, living facility density, and building density are the three indicators that most strongly influence urban vitality; each indication has a negligible impact on the temporal dimension of urban vitality. (3) The indicators in Tianjin’s core urban region have a substantial impact on urban vitality. Their threshold effect and non-linear influence are evident, and managing the indicators within a suitable range may effectively promote urban vitality. The study’s findings might serve as a foundation for Tianjin’s core city’s urban planning and design.